Crustal imprints of Precambrian orogenesis in western Laurentia. Issue 10 (12th October 2015) - Chen, Yunfeng; Gu, Yu Jeffrey; Dokht, Ramin M. H.; Sacchi, Mauricio D.
Abstract: Crustal low‐velocity zones (LVZs) have been reported in active orogens such as the Himalayas and the Andes but rarely in stable cratonic regions. In this study, we provide compelling evidence for a significant midcrustal LVZ beneath eastern‐central Alberta, an integral part of the Precambrian Canadian Shield covered by thick Phanerozoic sedimentary deposits. This 200 km wide, over 10 km thick midcrustal LVZ is well resolved by shear velocity inversions using P‐to‐S receiver functions from more than 4600 earthquakes. It is generally overlain by a high‐velocity upper crust in the depth range of 8–15 km, especially in western‐central Alberta, which coincides with the previously documented Winagami reflection sequence. We interpret the LVZ to be of granitic composition, potentially in connection with the crystallization of partially molten crust during the Paleoproterozoic eon. In addition to the Precambrian tectonic history of western Laurentia, which featured plate convergence conducive to crustal melting, our crustal model is further supported by (1) a moderate spatial correlation between the LVZ and heat flow, and (2) shear velocities consistent with that of granite. The well preserved Winagami reflection sequence and the LVZ are potential evidence of distinct episodes of magmatism and crust modification in the Precambrian basement of the Western Canada Sedimentary Basin. The existence of a broad crustal LVZ suggests extensive subduction, orogenesis, and crustal melting during the Precambrian assembly of the North American craton. Key Points: A midcrustal LVZ is observed in the Precambrian Canadian Shield LVZ is 10+ km thick and over 200 km wide with granitic composition LVZ is caused by the crust melting during the Precambrian orogenesis